Caught in the Crossfire: How Contradictory Information and Norms on Social Media Influence Young Women’s Intentions to Receive HPV Vaccination in the United States and China - Pan, Shuya; Zhang, Di; Zhang, Jingwen (Frontiers in Psychology, 2020)
This study uses online survey data from the U.S. and China to examine how contradictory information and social norms regarding HPV vaccines obtained through social media are related to young women’s attitudes and intentions surrounding HPV vaccination. The results show that exposure to contradictory information on social media had a greater negative association with intentions to receive HPV vaccination among the U.S. participants than among the Chinese participants, while social norms supporting HPV vaccines had a stronger positive association with intentions to receive HPV vaccination among the Chinese participants than among the U.S. participants. These findings extend the literature on social media communication regarding HPV vaccination and contribute to our knowledge of cultural contexts that influence intentions to receive HPV vaccination.